2002
DOI: 10.1191/0961203302lu176sr
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IL-16 levels in patients with systemic lupus erythematosus are associated with disease severity but not with genetic susceptibility to lupus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by several immunological abnormalities. The pathogenic importance of T cells in this disease is well established. Interleukin-16 (IL-16) is a cytokine which is mainly produced by CD8+ T cells and induces chemotaxis of CD4+ T cells and monocytes. IL-16 levels have been shown to be elevated in SLE patients in a cross-sectional study, but the mechanism is unknown. To explore whether the increased IL-16 levels are associated with genetic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 13 publications
3
24
0
1
Order By: Relevance
“…This observation would tend to favor the ''British Hypothesis'' that asthma and COPD (in particular, emphysema) are distinct diagnoses as opposed to the Dutch hypothesis, which postulates that the two diseases are related through a continuum of airway inflammation (Barnes, 2006). Although the role that IL-16 might play in emphysema and COPD is unknown, one possibility is that it is ( Lard et al, 2002;Lee et al, 1998), rheumatoid arthritis (RA) (Blaschke et al, 2001;Lard et al, 2004); bullous pemphigoid (Frezzolini et al, 2004), diabetes (Meagher et al, 2010), and preeclampsia (Gu et al, 2008). In a mouse model of rheumatoid arthritis, IL-16 attenuates joint inflammation (Klimiuk et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation would tend to favor the ''British Hypothesis'' that asthma and COPD (in particular, emphysema) are distinct diagnoses as opposed to the Dutch hypothesis, which postulates that the two diseases are related through a continuum of airway inflammation (Barnes, 2006). Although the role that IL-16 might play in emphysema and COPD is unknown, one possibility is that it is ( Lard et al, 2002;Lee et al, 1998), rheumatoid arthritis (RA) (Blaschke et al, 2001;Lard et al, 2004); bullous pemphigoid (Frezzolini et al, 2004), diabetes (Meagher et al, 2010), and preeclampsia (Gu et al, 2008). In a mouse model of rheumatoid arthritis, IL-16 attenuates joint inflammation (Klimiuk et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of rheumatoid arthritis, IL-16 attenuates joint inflammation (Klimiuk et al, 1999). However, IL-16 plasma levels are elevated during RA and SLE flare-ups in humans, suggesting that IL-16 may play a regulatory role rather than a pathogenic role (Blaschke et al, 2001;Lard et al, 2002;Lee et al 1998). Adoptive transfer experiments of IL-16 expressing CD8 + (suppressor) cells result in a marked reduction of autoimmunity in rheumatoid synovitis (Klimiuk et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to many chemokines, IL-16 has been detected at sites of inflammation in various inflammatory conditions, such as asthma, inflammatory bowel disease, rheumatoid arthritis, delayed-type hypersensitivity, multiple sclerosis, systemic lupus erythematosus, and Graves' disease (11)(12)(13)(14)(15)(16)(17). The precise role of IL-16 in these diseases has yet to be determined; however, it has now been shown that the exogenous administration of IL-16 in a murine model of acute allergic airway inflammation results in significant attenuation of both airway hyper-reactivity and lung inflammation (18).…”
mentioning
confidence: 99%